Pengaruh Kecerdasan Spiritual dan Keharmonisan Keluarga terhadap Kecenderungan Kenakalan Remaja Di MTs Negeri 1 Jombang - Siswati Siswati; Adibah Adibah (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2020)
This study aims to determine the effect of spiritual intelligence and family harmony on the tendency of juvenile delinquency in MTs Negeri 1 Jombang. Sampling using random cluster sampling technique, namely class VIII-B with 32 students. Collecting data using a spiritual scale, harmony scale and juvenile delinquency scale which refers to a Likert scale. The data analysis technique used non-parametric analysis of Spearman's rho level correlation. The results of the influence of the spearman's rho level between spiritual and delinquency were obtained rho = 0.195 and sig 0.285 (P> 0.05), meaning that there was no significant negative relationship between spirituality and delinquency in class VIII-B students of MTs Negeri 1 Jombang. The results of the influence of the spearman's rho level between harmony and delinquency were rho = 0.460 and sig 0.03 (P <0.05), which means that there is a significant positive relationship between harmony and delinquency in class VIII-B students of MTs Negeri 1 Jombang. The higher the krluarga harmony, the lower the juvenile delinquency tendency and conversely the lower the family harmony, the higher the juvenile delinquency tendency.